2011
DOI: 10.1002/jctb.2760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetic acid on lipid accumulation by glucose‐fed activated sludge cultures

Abstract: BACKGROUND: The effect of acetic acid, a lignocellulose hydrolysis by-product, on lipid accumulation by activated sludge cultures grown on glucose was investigated. This was done to assess the possible application of lignocellulose as low-cost and renewable fermentation substrates for biofuel feedstock production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Acetic acid thus served as both pH moderator and carbon feedstock. Considering that protonated acetic acid crosses the cellular membrane through passive transport and affects intracellular pH balance (20,21), the fermentation pH was maintained at 7, which is higher than the pK a of acetic acid. In this way, acetic acid existed primarily in the salt form, which is less toxic to the cells.…”
Section: Resultsmentioning
confidence: 99%
“…Acetic acid thus served as both pH moderator and carbon feedstock. Considering that protonated acetic acid crosses the cellular membrane through passive transport and affects intracellular pH balance (20,21), the fermentation pH was maintained at 7, which is higher than the pK a of acetic acid. In this way, acetic acid existed primarily in the salt form, which is less toxic to the cells.…”
Section: Resultsmentioning
confidence: 99%
“…29 With the inoculation rate increase, the initial acetic acid concentration decreased, which resulted in a lower inhibition effect on the biomass growth in the logarithmic phase. 40 Similarly, other toxic secondary metabolites as well as the solvent product from the ABE fermentation could also lead to a more severe inhibition to cell growth when the inoculation rate decreased. In the stable stage, the lack of nutrients led to the decrease of the biomass productivity in the high inoculation rate cases.…”
Section: Two-stage Abe Fermentationmentioning
confidence: 99%
“…Fortunately, the organic acid by-products in the fermentation broth could be metabolized as a carbon source by several oleaginous strains. [37][38][39][40][41] Aiming to reuse the high organics content wastewater from ABE fermentation processes and convert them into valuable advanced bio-fuels, while further decreasing the COD level, in the present study, an effective and energy saving biochemical process was performed to emphasize the 'green benefits' (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that activated sludge microbial consortia (ASMC) are capable of accumulating lipids when cultivated in a N-limited environment with abundant carbon sources, particularly when C/N mass ratio is ≥40. These previous works had the ultimate goal of utilizing existing WWTPs for production of microbial lipids, which can be used as bioenergy and/or biomaterial precursors. , This goal entails addition of aerobic lipid-accumulation unit(s) that utilizes additional carbon source or substrate to enhance microbial lipids production in ASMC. However, utilization of expensive substrates (e.g., sugars, lignocellulosic biomass hydrolyzates) could account for up to 75% of the costs of microbial lipids and thus, presents a major drawback in its large scale implementation …”
Section: Introductionmentioning
confidence: 99%